A Novel Exploration of the Impact of Social Media on the Tourism Industry of Bandar-e-Turkmen - Saber Arekhi (اکولوژی انسانی, 2023)
The tourism industry holds immense potential for growth and development. One of the most influential factors in promoting tourism is advertising and information dissemination through digital platforms. Social media plays a decisive role in cultural awareness, education, information dissemination, and fostering social participation in the development of the tourism industry. With the expansion of information and communication technology, social media has become a key tool for attracting and engaging tourists.This study investigates the impact of social media on the tourism industry in Bandar-e-Turkmen. The objective of the research is to analyze the relationship between the use of social media, tourists' emotions, and the quality of brand relationships as factors influencing tourist attraction. The research was conducted using a survey method, with a questionnaire distributed among 374 residents and tourists in Bandar-e-Turkmen. Data were analyzed using statistical methods, including regression analysis and correlation tests.The results indicate that social media usage for 1 to 10 hours per day has a positive and significant impact on tourists' emotions, whereas usage exceeding 11 hours has a negative effect. Additionally, a direct and significant relationship was identified between social media usage and the quality of brand relationships, which influences tourist attraction. These findings can assist policymakers and tourism industry stakeholders in enhancing advertising strategies and improving service quality, thereby creating more positive experiences for tourists and ultimately increasing tourist attraction.